Influencia de la variación climática, en relación con los recursos productivos en dos comunidades de la parroquia Cusubamba, provincia de Cotopaxi. - Padilla Yanchatipan, Guadalupe Elisabeth (2023)
This study focused on investigating the relationship between climate variation and productive resources in two communities in the Cusubamba parish, Cotopaxi province. The objectives of the study included the identification of climate data for the last 30 years obtained from the platform of the National Aeronautics and Space Administration (NASA, 2022) in the communities of Carrillo and Compañía Baja, the analysis of climate variation in crops of corn and potatoes and the socialization of the participatory tool called Pacha grama for decision making in agriculture in both communities. With the identification of the data from the period 1990 to 2020 from the NASA platform, the behavior of the climatic variables, precipitation and temperature of the communities, was analyzed and through the application of a survey carried out on a total of 90 people, that is, 45 people per community; The results obtained revealed that 100% of the people in the two communities perceive climate change, which is related to NASA data; In this sense, climate variability has become more evident in the last 20 years and can affect corn and potato crops, especially due to the variation in precipitation as seen in the NASA record of the last 20 years. which shows 14 years with annual averages of precipitation between 378 ml and 496 ml, insufficient quantities for potato and corn crops, which require around 500 ml to 700 ml, according to INIAP (2008). Furthermore, during the socialization of Pacha grama it was observed that people had difficulties in recording agroclimatic data, consequently, a continuous socialization process is necessary.